MAGNETIC MEMORY AND COUPLING BETWEEN SPIN-CANTED AND DEFECT MAGNETISM IN HEMATITE - Özdemir Ö.; Dunlop D.J. (My University, 2006)
Saturation isothermal remanent magnetization (SIRM) has been studied on submicron hematite powders with grain sizes between 0.12 and 0.52 μm and on 2 to 5 mm natural hematite single crystals before and after zero-field cycling through the Morin transition (TM). SIRM cooling and warming curves for single-domain (SD) crystals are similar to those of multidomain (MD) hematites. Both have similar remanence losses at TM (97-98% of the original SIRM), a similar defect moment below TM (2-3% of initial SIRM), and similar memory (30-40% of initial SIRM). Regardless of grain size, higher SIRM memory ratios are associated with higher defect moments below TM. In SD and MD hematites alike, room temperature magnetic memory seems to be an amplification of residual weak ferromagnetism that persists even at very low temperatures, much below TM. Applying a strong field to initially demagnetized SD and MD hematites at 20 K produced a substantial SIRM, which spontaneously increased by a factor 10-28 upon crossing the transition at TM. These observations imply that some spins do not participate in the general rotation Erom the ferromagnetic c plane to the antiferromagnetic c axis below TM. The defect moment of these spins serves to restore preferred directions of spins and ferromagnetic domains during zero-field warming through the Morin transition and is thus responsible for the memory phenomenon. The existence of a weak ferromagnetic moment in antiferromagnetic hematite below TM, is also indicated by colloid patterns observed by Gallon. We propose that the mechanism of memory is clusters of spins pinned magnetoelastically by lattice defects. These spins rotate only partially out of the basal plane during cooling through TM. Some basal plane anisotropy, also magnetoelastic in origin, must remain below TM in order to explain the existence of low-temperature SIRM and also to guide spin nuclei into preferred orientations above TM on rewarming through the transition in zero field. Copyright 2006 by the American Geophygical Union.